2010
DOI: 10.1016/j.acuro.2010.02.019
|View full text |Cite
|
Sign up to set email alerts
|

Evaluación del test PCA3 para el diagnóstico de cáncer de próstata: revisión sistemática y metanálisis

Abstract: Original-Cá ncer de pró stata Evaluació n del test PCA3 para el diagnó stico de cá ncer de pró stata: revisió n sistemá tica y metaná lisis J. Ruiz-Aragó n à y S. Má rquez-Pelá ez Agencia de Evaluació n de Tecnología Sanitaria de Andalucía (AETSA), Consejería de Salud, Junta de Andalucía, Españ a informació n del artí culo Historia del artículo: Recibido el 1 de febrero de 2010 Aceptado el 6 de febrero de 2010 On-line el 10 de abril de 2010 Palabras clave: Cá ncer de pró stata Diagnó stico PCA3 Detecció n prec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(4 citation statements)
references
References 28 publications
(48 reference statements)
1
3
0
Order By: Relevance
“…Additionally, Madeira et al (2015) reported a global diagnostic OR of 38.92 (95% CI (17.82–84.99); Q = 41.2, p = 0.0001; I 2 = 73.3%). These results are similar to those obtained in the current meta-analysis in as much as their OR value is high and statistically significant, although the confidence interval was substantially wide [40,41]…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Additionally, Madeira et al (2015) reported a global diagnostic OR of 38.92 (95% CI (17.82–84.99); Q = 41.2, p = 0.0001; I 2 = 73.3%). These results are similar to those obtained in the current meta-analysis in as much as their OR value is high and statistically significant, although the confidence interval was substantially wide [40,41]…”
Section: Discussionsupporting
confidence: 88%
“…This is ratified by the results obtained in this paper and others, such as the meta-analysis proposed by Ruiz and Márquez (2010), who evaluated the detection of the PCA3 gene product through antigen detection in urine samples, as a biomarker for prostate cancer. This group of researchers reported heterogeneity in global sensitivity and specificity of 63% and 74%, respectively, and reported an area under the curve of 0.73 [41].…”
Section: Discussionmentioning
confidence: 99%
“…The diagnostic value of the PCA3 score in patients demonstrated a sensitivity of 46-82%, specificity of 56-89%, PPV of 59-97% and negative predictive value (NPV) of 87-98% 63 - 66 . Such variability can be explained by the fact that different inclusion criteria, cut-off values and protocols were used in these studies.…”
Section: Detection Of Prostate Cancer Biomarkers In Clinical Samplesmentioning
confidence: 99%
“…Given this situation, new diagnostic methods have emerged, such as prostate cancerspecific antigen 3 (PCA3), which is a marker that detects overexpression of the PCA3 gene by molecular techniques. As the name implies, PCA3 is specific for prostate cancer, and it is expressed only in this disease and is not affected by benign conditions, as occurs with PSA, thereby decreasing the risk of false positives [3].…”
Section: Introductionmentioning
confidence: 99%